Analysis and optimization of control cam mechanism in a roller-type corn finger planter based on DEM and MBD coupling technology - Deng, Tinghao; Zhao, Wuyun; Shi, Linrong; Sun, Bugong; Qi, Tianshan; Li, Hui (International Journal of Agricultural and Biological Engineering, 2025)
The application of plastic mulch in the arid regions of northwest China has demonstrated significant advantages, making roller-type hole sowing on mulch a key agricultural trend. In order to enhance the performance of a roller-type corn finger planter equipped with finger pickups. This study analyzed the motion patterns of corn seeds within the device and investigated the effects of control cam parameters, including pickup section, vibration section, pickup stroke angle, and torsion spring force, on seed-metering performance. Using DEM-MBD coupling technology, single-factor experiments and second-order orthogonal rotational combination simulation experiments were conducted. The optimal parameter is that pickup section stroke angle is 78.98°, vibration section stroke angle is 20.07°, and a normal force is 2.99 N, which was validated through bench tests, achieving a seed-metering qualification rate of 93.86%, a missed seeding rate of 3.19%, and a reseeding rate of 2.95%. These results met the standards and agronomic requirements, demonstrating the effectiveness of the proposed optimization method. It provides a foundation for improving the precision and reliability of roller-type corn seed-metering devices. Keywords: corn, roller-type corn finger planter, control cam, DEM-MBD, coupling simulation DOI: 10.25165/j.ijabe.20251801.9322 Citation: Deng T H, Zhao W Y, Shi L R, Sun B G, Qi T S, Li H. Analysis and optimization of control cam mechanism in a roller-type corn finger planter based on DEM and MBD coupling technology. Int J Agric & Biol Eng, 2025; 18(1): 143–153.